The Plight Of Being Black Reflected In Tate Taylor's The Help Movie (2011): A Marxist Approach - Maulida, Dina, Dr. Phil. Dewi Candraningrum, M. Ed, Drs. Abdillah Nugroho, M.Hum (2013)
In this study is primarily proposed to analyze how the plight of being black reflected in Tate Taylor's The Help movie (2011) viewed from Marxist approach, and to analyze the movie based on its structural elements. The writer uses Karl Marx's Marxism theory to answer the problem of the study. In analyzing The Help movie, the writer conducts the study by using a descriptive qualitative study that it has data in the form of written or oral from observing people or behavior and Marxist approach. There are two data source in this study, primary and secondary data. The primary data source is the play of The help movie itself and the secondary data source are the sources that relate to the primary data, such as author's biography, books or e-books, journal, internet or any information relate the issue of this study "the plight of being black" and social background of American society in the middle twentieth century. The data are collected by using two kinds of technique, the first is note taking and the second is image capturing. The result of this study shows that there is plight of being black in America at the 1960's period. At the time the struggle to be equal for taking out from segregation era is difficult to achieve. In The Help movie (2011), Tate Taylor wants to show that this is the real life happened in America, and he wants to tell that there is no separated treatment in human although each people have different color, culture, ideology, and the like.